Structural Elucidation of Some Phenolic Compounds from the Leaves of Kadsura Coccinea in Vietnam - Le, Thi Thuy; Tran, Thu Huong; Le, Huyen Tram; Nguyen, Hai Dang (JST: Engineering And Technology For Sustainable Development, 2022)
Natural products and their derivatives represent more than 50% of all the drugs in modern therapeutics. Flavonoids and lignans are large group of naturally occurring and play a variety of biological activities in plants. Schisandraceae family includes 2 genera, Schisandra and Kadsura with about 39 species of plants. The Kadsura coccinea, belonging to Schisandraceae family, is mainly distributed in the tropical and subtropical regions of South and Southeast Asia. The aim of this study is the isolation and structural elucidation of compounds isolated from the leaves of Kadsura coccinea. For this purpose, five known flavonoid compounds, (+)-gallocatechin (1), catechin (2), (-)-epicatechin (3), phloretin-2-O-glucoside (4), phloretin-4-O-glucoside (5) together with 2-hydroxy-5-methoxyphenyl-O-β-D-glucopyranoside (6) and icariside E3 (7) were isolated. Their structures are elucidated by NMR spectroscopic analysis as well as compared with the literature. Especially, compound 6 is the first isolated from this plant.